1991
DOI: 10.1042/bj2760113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of release of basic fibroblast growth factor from bovine retinal endothelial cells in monolayer cultures

Abstract: Release of basic fibroblast growth factor (bFGF) was investigated in bovine retinal endothelial cells (BREC) maintained in monolayer culture. Confluent cells released bFGF into serum-free culture medium or medium containing 5 % serum at rates of up to 105.2 and 61.3 pM/day respectively. bFGF release coincided with a decrease in monolayer cell number and increases in lactate dehydrogenase (LDH) concentration and cells and cell-debris particles in the medium, which suggested that cell damage and lysis were respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Further supporting the idea that FGF-2 is pre-loaded in endothelium and released during apoptosis were ELISA data demonstrating the presence of the growth factor in both non-apoptotic and apoptotic HUVEC, as well as increasing levels of FGF-2 in culture supernatants during apoptosis. These observations were consistent with an earlier report demonstrating the presence of FGF-2 in the culture supernatants of bovine endothelium after 6 days of serum deprivation [51]. Exogenously added FGF-2 appeared comparatively inactive compared with that manufactured endogenously by the cells, in that much higher protein levels of exogenous FGF-2 were required to mediate an effect comparable to endogenous FGF-2 detected by ELISA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further supporting the idea that FGF-2 is pre-loaded in endothelium and released during apoptosis were ELISA data demonstrating the presence of the growth factor in both non-apoptotic and apoptotic HUVEC, as well as increasing levels of FGF-2 in culture supernatants during apoptosis. These observations were consistent with an earlier report demonstrating the presence of FGF-2 in the culture supernatants of bovine endothelium after 6 days of serum deprivation [51]. Exogenously added FGF-2 appeared comparatively inactive compared with that manufactured endogenously by the cells, in that much higher protein levels of exogenous FGF-2 were required to mediate an effect comparable to endogenous FGF-2 detected by ELISA.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, however, neutralizing antibodies against FGF-2 failed to inhibit the earlier reported activity, so that the identity of the reported protective factor is uncertain [52]. Insulin-like growth factor-1 is released along with FGF-2 when bovine retinal endothelial monolayers are wounded by scraping [51], while platelet-derived growth factor has also been detected in media of injured bovine aortic endothelium [39], and it is possible that these cytokines play a similar role to FGF-2 in protecting against endothelial apoptosis. An earlier study demonstrated increased synthesis and release of Fas ligand by non-apoptotic endothelium in hypoxic conditions, with the effect of reducing hypoxia-induced apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…bFGF is well known to have no signal peptide for its secretion [1], and may be passively released by cell damage or death [3,17,33,38,42]. In this study, as the LDH levels in the CM were not increased and no cell damage or death of cancer cells was apparent under hypoxic cultivation.…”
Section: Discussionmentioning
confidence: 54%
“…10). In ischemic retinopathies where bFGF and VEGF are thought to play significant roles, damaged and dying retinal cells release bFGF (74). In addition, bFGF stored in the extracellular matrix can be released as a bioactive bFGF-glycosaminoglycan complex (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%